Three Case Studies of the Language Used to Justify Recent Neoliberal and Neoconservative Curricular Reform - Di Giovanni, Adamo; Parker, Lana (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2025)
The overarching objective of this study is to become more closely attuned to the politics of curriculum by identifying the discursive practices employed by governments to position curricular reform. In particular, this analysis aims to show how the twinning of neoliberalism and neoconservatism has served to justify shifts in curriculum at three North American sites in recent years. Further, using rhetorical analysis as a form of critical discourse analysis, the study demonstrates how discursive tools are used to advance neoliberal and neoconservative values under the guise of a taken-for-granted sense of education’s purpose and role. Rather than an analysis of curriculum documents as texts, this study focuses on government rhetoric describing the rationale for curricular reform so as to better recognize which values are gaining formal power, offer clarity into what is oppressed or ignored, and, ultimately, provide insights into where resistance might be aimed.